2001
DOI: 10.1021/bi010592d
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Exosite on Coagulation Factor VIIa and Its Molecular Interactions with a New Class of Peptide Inhibitors

Abstract: A new inhibitory peptide binding exosite on the protease domain of coagulation Factor VIIa (FVIIa) has been identified. A novel series of peptide inhibitors of FVIIa, termed the "A-series" peptides, identified from peptide phage libraries and exemplified by peptide A-183 [Dennis, M. S., Roberge, M., Quan, C., and Lazarus, R. A. (2001) Biochemistry 40, 9513-9521], specifically bind at a site that is distinct from both the active site and the exosite of another recently described peptide inhibitor of FVIIa, E-76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 45 publications
(90 reference statements)
1
61
0
Order By: Relevance
“…Under these conditions, the apparent velocity of FX hydrolysis by FVIIaWT was significantly higher than that of FVIIa303T. This finding suggests that the conformational equilibrium FVIIa « FVIIa*, where FVIIa is the zymogen-like form and FVIIa* is the functionally active form of the FVIIa molecule (Dennis et al, 2000Persson et al, 2001a;Roberge et al, 2001;Sichler et al, 2002), is severely shifted to the right. The perturbation of this conformational equilibrium is even more evident in the presence of TF, whose binding is unable to shift the conformational transition toward a fully active FVIIa form.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Under these conditions, the apparent velocity of FX hydrolysis by FVIIaWT was significantly higher than that of FVIIa303T. This finding suggests that the conformational equilibrium FVIIa « FVIIa*, where FVIIa is the zymogen-like form and FVIIa* is the functionally active form of the FVIIa molecule (Dennis et al, 2000Persson et al, 2001a;Roberge et al, 2001;Sichler et al, 2002), is severely shifted to the right. The perturbation of this conformational equilibrium is even more evident in the presence of TF, whose binding is unable to shift the conformational transition toward a fully active FVIIa form.…”
Section: Discussionmentioning
confidence: 87%
“…Both these interactions inhibit, in a non-competitive way, FVIIa activity toward FX and synthetic amide substrates (Dennis et al, 2000Roberge et al, 2001). In contrast, recent studies showed that polyethylene glycol binds to a region located in proximity to the 60s loop, enhancing the enzyme function (Sichler et al, 2002).…”
mentioning
confidence: 99%
“…Examples of this class include peptide inhibitors of factor VIIa (67,68) and small molecule inhibitors of ␤-lactamase (69). Very recently, a novel allosteric peptide, pep419, which binds near the 90s helix in caspase-6 inducing a tetrameric state, has been reported to function via this second class of allosteric mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This was carried out by first combining two halves of the protease domain, one from the A-183⅐FVII zymogen structure (16,18) and the other from the TF⅐FVIIa structure (31). The rationale for this derives from the protease architecture (two distorted ␤-barrels) and the largely independent effects of A-183 in one barrel and the presentation of the S 1 subsite in the other barrel.…”
Section: Methodsmentioning
confidence: 99%
“…Here we have pursued a new strategy to obtain less complex peptide exosite inhibitors that are both specific and complete. The crystal structure of the protease domain of FVII in complex with A-183 revealed that its C terminus was in close proximity to the active site (16,18). This suggested that extending its C terminus into the active site region should result in a chimeric peptide having a high degree of specificity and potency due to its exosite interactions and more complete inhibition due to greater steric hindrance in the substrate binding cleft of the active site.…”
mentioning
confidence: 99%